PEMBERDAYAAN EKONOMI MELALUI INOVASI PRODUK OLAHAN IKAN NILA DAN STRATEGI PEMASARAN DIGITAL MELALUI PROGRAM DESA WIRAUSAHA DI DESA SEJEGI, KABUPATEN MEMPAWAH - Diva Cahya Nayla; Dedi Herdiansyah; Shelvi, Shelvi; Divana Syakila Putri; Fanny Fadillah Nurrahmah; Aditya Pratama; Andre Setyawan (Bajang Institute, 2025)
Background: Sejegi Village, Mempawah Timur Subdistrict, Mempawah Regency, is located approximately 84 km from the Politeknik Negeri Pontianak campus. The community has diverse occupations, including farmers, planters, civil servants, daily laborers, traders, and private employees. A survey conducted by HMJ AB Polnep revealed that Sejegi Village has significant potential in the fisheries sector, particularly in tilapia aquaculture, with cages and hatcheries covering approximately 2 hectares. The cultivation cycle takes 4–7 months; however, most of the harvest is sold raw, while processed products such as nuggets and fish balls remain limited. Program Method: The program employed potential identification surveys, preparation of activity proposals, tilapia processing training into abon and nuggets for PKK mothers, digital marketing training for Karang Taruna youth, mentoring, evaluation, and dissemination of results to stakeholders, including the campus, village government, and ministries. The program emphasizes active community participation to apply skills practically. Results Achieved: PKK mothers are able to produce tilapia-processed products regularly, while Karang Taruna youth actively market the products via social media. Community mindset has shifted from selling raw fish to becoming creative entrepreneurs based on local processed products. The program enhances skills, strengthens community collaboration, encourages village economic growth, and ensures the sustainability of production. These activities provide tangible socio-economic impacts and support the achievement of Sustainable Development Goals (SDGs), particularly in promoting health and welfare, with the flagship product being Tilapia Nuggets.